Effects of ablative and non-ablative laser shock peening on AA7075-T651 corrosion and fatigue performance. Issue 12 (13th August 2021) - Sanchez, A. G.; Leering, M.; Glaser, D.; Furfari, D.; Fitzpatrick, M. E.; Wharton, J. A.; Reed, P. A. S.
Abstract : The fatigue performance from pre-corroded pits was studied in laser-shock-peened AA7075-T651 with and without a protective ablation-layer. Surface and microstructural characterisation showed laser-shock-peening generated residual stresses up to −400MPa, limited hardness and moderate surface roughness increase. The laser-shock-peened specimens were exposed to 3.5 wt-% sodium chloride solution for different levels of galvanostatic control. The compressive residual stresses did not significantly affect corrosion behaviour, or corrosion pit morphology. Laser-shock-peening-induced surface roughness had the most detrimental impact on corrosion performance. Fatigue testing of pre-corroded AA7075-T651 showed pits act as stress concentrations. Cracks initiated shortly after dynamic loading, reducing fatigue life by 50%. Laser-shock-peening increased fatigue life by 400% compared to corroded-untreated AA7075-T651, due to residual stresses effectively counteracting stress concentrations produced by pits. Highlights Pre-corroded laser-peened (LSP and LSPwC) AA7075-T651 fatigue performance is investigated. XRD and incremental hole drilling show deeper compressive residual stresses for LSPwC compared to LSP. Electrochemical tests show no significant changes in corrosion behaviour after laser peening. Fatigue testing and fractography show compressive residual stresses effectively counteract stress concentrations at pits.